ANALISIS KINERJA KARYAWAN PADA PT. BANK MANDIRI (Persero), Tbk. CABANG CENDRAWASIH MAKASSAR - Gadis Gayatri; Amir Imbaruddin; Muttaqin Muttaqin (Politeknik STIA LAN Makassar, 2018)
Abstract The current era of globalization requires companies to always adjust their strategies to changes that occur in order to survive or guarantee the continuity of the company. Human resources are the main role in every company activity. Despite many facilities and infrastructures, without the support of human resources, the company's activities will not run well. To achieve company goals, employees are required to maximize their performance. The purpose of this study was to determine and analyze how employee performance appraisal at PT. Bank Mandiri (Persero) Tbk. Cendrawasih Makassar Branch, with a qualitative approach, and using instruments through interviews, observation and document review. While data collectiotechniques are through interviews, observation and document review. Data processing technique is descriptive analysis. The result of the study shows that most employees finish their work based on the estimated targets and are capable to increase the demand of loan credit. Judging the aspect of the quality of the work, the level of error in completing the work is still low and besides that, each employee complete the work according to the specified objectives. Judging from the timeliness aspect, employees have the ability to complete each job in a timely manner. Judging the aspect of attendance, that employee attendance is relatively high because employees attend the office on time. While in terms of the ability to cooperate, this study found that employees in doing work always establish cooperation with other colleagues and collaborate in a teamwork and maintain good relationship between superiors and subordinates.